Representasi Nilai Perdamaian di Buku Pembelajaran Bahasa Inggris: Analisis Wacana Kritis - Turnip, Cicilia; Yanto, Elih Sutisna (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
Textbook can be as a medium to convey values, while teachers and learners enact as the values- carrying agents. This present study aims to investigate peace value in national ELT textbook which approved by Indonesian Ministry of Educational and Culture entitled Bahasa Inggris untuk SMA/MA/SMK/MAK Kelas XII [English for Senior High School Grade XII]. Findings show that there are three basic sources of peace value such as inner peace (building learner’s self-concept), social peace (tolerance with differences) and peace with nature (take care of the environment). This critical discourse analysis study indicates that social practice can be identified through language. Thus, it will contribute for both students and teachers in order to be aware as value agent in ELT textbook.